1990
DOI: 10.1017/s0031182000060601
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological significance of vector–parasite interactions

Abstract: A great deal of published experimental evidence shows that parasite-induced changes in host choice, and biting and survival rates of bloodsucking insects are an important source of bias in estimates of Vectorial Capacity. I argue here that, because of the difficulties of handling these and other biases in practice, indices (based on the Vectorial Capacity) which purport to measure transmission rate are best used in a comparative rather than an absolute way. They should attempt to measure, not transmission rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, the C values considered here range from 3.7 to 29.2, in accord with field estimates [33-38, but see [39][40], so if we consider 1/(DH+WN) roughly equivalent to r, then k ranges from 30b to 50b. Even if we consider the b-equivalent values in our model as ranging from 0.1 to 1 (k values from 3 to 50), field estimates span the resulting range of Z 0 values.…”
Section: Discussionsupporting
confidence: 79%
“…However, the C values considered here range from 3.7 to 29.2, in accord with field estimates [33-38, but see [39][40], so if we consider 1/(DH+WN) roughly equivalent to r, then k ranges from 30b to 50b. Even if we consider the b-equivalent values in our model as ranging from 0.1 to 1 (k values from 3 to 50), field estimates span the resulting range of Z 0 values.…”
Section: Discussionsupporting
confidence: 79%
“…Life histories and vectorial capacities of phlebotomines may have direct effect on the incidence of leishmaniasis. [19][20][21] In Lutzomyia, vectorial capacity is highly species specific; 8,22,23 thus, it may vary significantly between cryptic species. Furthermore, clinical manifestation of leishmaniasis has also been found to vary between geographic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, p is estimated by P 1/u , where p is the daily probability of survival, P is the parity rate of Þeld-captured midges, and u is the length of the gonotrophic cycle. Dye (1990) suggested that using the parous rate to determine survivorship works reasonably well when the aim is to measure comparative change in vectorial capacity.…”
Section: Methodsmentioning
confidence: 99%